MRNA expression profiles in circulating tumor cells of metastatic colorectal cancer patients. Issue 4 (21st January 2015) - Mostert, Bianca; Sieuwerts, Anieta M.; Bolt-de Vries, Joan; Kraan, Jaco; Lalmahomed, Zarina; van Galen, Anne; van der Spoel, Petra; de Weerd, Vanja; Ramírez-Moreno, Raquel; Smid, Marcel; Verhoef, Cornelis; IJzermans, Jan N.M.; et al.
Abstract : Introduction: The molecular characterization of circulating tumor cells (CTCs) is a promising tool for the repeated and non‐invasive evaluation of predictive and prognostic factors. Challenges associated with CTC characterization using the only FDA approved method for CTC enumeration, the CellSearch technique, include the presence of an excess of leukocytes in CTC‐enriched blood fractions. Here we aimed to identify colorectal tumor‐specific gene expression levels in the blood of patients with and without detectable CTCs according to CellSearch criteria. Materials and methods: Blood of 30 healthy donors (HDs) and 142 metastatic colorectal cancer (mCRC) patients was subjected to CellSearch CTC enumeration and isolation. In all samples, 95 mRNAs were measured by reverse transcriptase quantitative PCR (RT‐qPCR). HD blood samples and patient samples with three or more CTCs were compared to identify CTC‐specific mRNAs. Patient samples without detectable CTCs were separately analyzed. Results: Thirty‐four CTC‐specific mRNAs were higher expressed in patients with ≥3 CTCs compared with HDs (Mann–Whitney U‐test P < 0.05). Among patients without detectable CTCs, a HD‐unlike subgroup was identified which could be distinguished from HDs by the expression of epithelial genes such as KRT19, KRT20 and AGR2. Also, in an independent patient set, a similar HD‐unlike group could be identified among the patients without detectable CTCs according to the CellSearch system. Conclusion: Extensive molecular characterization of colorectal CTCs is feasible and a subgroup of patients without detectable CTCs according to CellSearch criteria bears circulating tumor load, which may have clinical consequences. This CTC‐specific gene panel for mCRC patients may enable the exploration of CTC characterization as a novel means to further individualize cancer treatment. Highlights: We measure the expression of 95 mRNAs in enriched circulating tumor cells (CTCs). We identify CTC‐specific mRNAs based on which three patient clusters are identified. A subgroup of patients without detectable CTCs differed from healthy donors. This distinction was driven by the expression of various epithelial genes. A similar HD‐unlike subgroup was identified in an independent patient set.